Factors Influencing the Compulsive Purchase of Personal Protective Equipment during the Covid-19 Pandemic Era - Krisna Rizky Febrianto; Farida Indriani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to examine the impact of compulsive buying on the purchase of personal protective equipment during COVID-19. Data were collected from a sampling population in Jakarta aged 17-35 years. This study used 164 respondents with purposive sampling method. The data obtained is processed using SPSS software. The findings show that all the variables used have a positive and significant effect on compulsive buying. In Hypothesis 1, the most influential indicator of self-conformance is x1.1 Consumer own Self-image. Hypothesis 2 for the variable Materialism has the most influential indicator is x2.2 Possession defind success. Hypothesis 3 for the utility value variable has the most influential indicator is x3.2 service. Hypothesis 4 for hedonic value has the most influential indicator is x.4.5 the thrill of the hunt. Hypothesis 5 for greed has the most influential indicator is x5.3 conscientiousness. The results also show that the most influential variable is materialism.